교육학 분야에서 CiteSpace에 기초한 구성주의 연구 동향 탐색 - 장위신(Yuxin Jiang); 송선희(Sun-Hee Song) (한국콘텐츠학회 논문지, 22(5), 2022)
As an important branch of cognitive psychology, "constructivism" is called a "revolution" in contemporary educational psychology, which has a profound influence on the field of pedagogy and psychology. Based on "WOS" database, this study selects "WOS Core database" and "KCI database", uses CiteSpace visualization software as analysis tool, and makes knowledge map analysis on the research literature of "constructivism" in the field of education in recent 35 years. Analysis directions include annual analysis, network connection analysis by country(region) branch, author, institution or University, and keyword analysis. The purpose of the analysis is to grasp the subject areas, research hotspots and future trends of the research on constructivism, and to provide theoretical reference for the research on constructivism. There are three conclusions from the study. 1. Studies on the subject of constructivism have continued from the 1980s to the present. It is now in a period of steady development. 2. Countries concerned with the subject of constructivism mainly include the United States, Canada, Britain, Australia and the Netherlands. The main research institutions and authors are mainly located in these countries. 3. Currently, the keywords constructivism research focus on the clusters of "instructional strategies", and the development of science and technology is affecting individual learning. In the future, instructional strategies will become the focus of structural constructivism research. With the development of instructional technology, it is necessary to conduct research related to the development of new teaching models. 구성주의는 인지심리학의 중요한 한 갈래로 현재 교육학 분야와 심리학 분야에 모두 커다란 영향을 미치고 있다. 본 연구는 CiteSpace 시각화 소프트웨어를 분석 도구로 사용하여 최근 35년간 교육분야에서 구성주의에 관한 연구문헌에 대한 지식지도 분석을 하였다. 이를 위하여 'WOS(web of science)' 데이터베이스를 기초로 국외문헌분석을 위하여 'WOS 핵심 데이터베이스'의 문헌들을 사용하였고, 국내문헌분석을 위하여 'KCI(Korean Journal Database)데이터베이스'의 문헌들을 분석하였다. 분석 방향은 발표연도, 연구가 이루어진 국가(지역), 연구자, 기관 또는 대학별 협력관계 분석, 주제어 분석이었다. 연구를 통해 얻은 결론은 세 가지이다. 첫째, 구성주의라는 주제에 관한 연구는 1986년부터 지금까지 이어지고 있으며 현재는 안정적인 발전단계이다. 둘째, 구성주의라는 주제로 연구가 많이 이루어진 국가는 미국, 캐나다, 영국, 호주, 네덜란드 순이다. 연구의 주요 기관과 연구자도 주로 이들 국가에 분포돼 있다. 셋째, 현재 구성주의 연구들의 주제어는 'instructional strategies(교수전략)' 집합에 집중되어 있으며, 과학기술의 발전이 개인 학습에 영향을 미치고 있다. 향후 교수전략은 구성주의 연구의 중점내용이 될 것이며, 교수공학의 발달로 새로운 교수모델 개발과 관련된 연구가 이루어질 필요가 있다.